Indirect Determination of Thiosulphate in Water by Atomic Absorption Spectrometry - Ghazy, S.E.; Kabil, M.A.; El-Defrawy, M.M. (Asian Journal of Chemistry, 2012)
A simple procedure for indirect atomic absorption spectrometric (AAS) determination of trance thiosulphate has been described. Thiosulphate ions form complex with silver ions. Silver thiosulphate complex is completely floated by oleic acid (HOL) surfactant at pH ≤ 3 in nitric acid medium. The procedure depends on adding known excess of Ag+ to the analyte S2O32– solution. After flotation, under the optimum conditions, the unfloated Ag+ is directly determined by AAS. The effects of some cations, anions and temperature on the flotation efficiency of silver thiosulphate and determination of excess silver have been examined. The procedure was successfully extended to determine trace thiosulphate added to tap water.